Comparative Analysis of Armed Conflicts in Africa: A Study on the Republics of Mali and Cameroon - Hamidu, Ishaku; Boyi, Ramatu; Hellandedu, Akaknaya Wesley; Kibikiwa, Minnessi Glenn (Kashere Journal of Politics and International Relations, 2025)
The work made use of secondary data and adopted conflict theory, this study revealed that various African nation-states faced challenges to include but not limited to trans-border crimes, sickness and diseases (like Malaria, Ebola, Polio); poverty, human trafficking; military intervention in politics, desert encroachments, to mention but a few. Majority of the states in the sub-region were colonial creations, Mali and Cameroon were for instance colonized by France before being granted independence. The sovereignty of both countries were however, at different times challenged by internal armed conflicts orchestrated either by ethnic militia and secessionists or religious extremists like the Tuaregs in Mali and the Ambazonian boys in the North-West and South-West regions of Cameroon. The similarities and differences between the two armed conflicts are examined. The paper concluded that the armed conflicts have negative impacts on each of the states, its economy, social infrastructures and the continent at large. Some recommendations to forestalled future and amicably resolve such or similar conflicts were outlined.